"Trust But Verify": How middle managers in a multinational use proverbs to translate an imported management concept. Issue 10 (October 2021) - Outila, Virpi; Piekkari, Rebecca; Mihailova, Irina; Angouri, Jo
In this paper we report on how middle managers in a Russian subsidiary translate empowerment, a 'western' management concept imposed by the Finnish headquarters. The analysis shows that in their discursive struggles these middle managers mobilised proverbs to address competing discourses that reflected imported and local ideals of good management. We advance organisational translation research by highlighting the value of proverbs as an understudied discursive resource in translation activities on the ground. The paper also examines the dual role of middle managers as both translators and implementers of an imported and imposed concept in a multinational corporation. Translation work carried out by middle managers in multinationals has received limited attention in previous research. Finally, by bringing together the discursive and the interlingual, we join recent efforts to broaden the definition of translation to encompass translation work undertaken in multilingual organisations.